Material dependencies: hidden underpinnings of sustainability transitions - Kristof Van Assche; Martijn Duineveld; Raoul Beunen; Vladislav Valentinov; Monica Gruezmacher (Journal of Environmental Policy & Planning, 2022)
This paper presents a framework for analysing the different ways in which materiality impacts environmental policy and governance. It draws on notions from the wider literature on materiality and integrates relevant insights into a theory on policy and governance. Building on a key distinction between the material and the discursive dimensions of governance, it develops the concepts of material events and material dependencies. Material events bring attention to the linkages between material changes and their observation and interpretation in governance. The concept of material dependencies is useful for analysing the different ways in which materiality structures the evolution of governance systems. The paper ends with some methodological considerations for mapping and analysing material dependencies and suggestions for further research.
Keywords: 330; materiality; sustainability; environmental governance; discourse; socio-technical transition theory